3D Printing for scaphoid-reconstruction with medial femoral condyle flap. Issue 12 (December 2020) - Schmidt, Manfred; Holzbauer, Matthias; Kwasny, Oskar; Huemer, Georg M.; Froschauer, Stefan
Highlights: Our article introduces the use of 3D printed models of the proximal scaphoid pole as an aid for elevation of vascularized osteochondral grafts from the medial femoral condyle for reconstruction of scaphoid non-union. Usage of these custom-made device critically eases positioning and customizing of flap donor site. Furthermore, elevation of oversized flaps is avoided, thus minimizing donor site morbidity. Abstract: Three-dimensional (3D) printing has emerged as an innovative technology to derive a maximum benefit from high-resolution tomography images and virtual 3D reconstructions. The present study describes a novel technique using a 3D printed model for harvesting osteochondral medial femur condyle (MFC) flap to replace the proximal pole of the scaphoid in case of proximal avascular pole. MFC bone grafting has already proved to be reasonable surgical method for this indication. To refine this technique, we introduce a 3D model of the proximal scaphoid pole on a handlebar with anatomic orientation marks on its surface, which was virtually planned via 3D imaging and finally 3D printed. This 3D model was sterilized and facilitated several intraoperative steps, such as resecting the proximal pole, simulating the alignment of the future MFC flap, detecting the most feasible harvest site, reducing the donor site morbidity and precisely modeling the graft. In summary, 3D printing is an innovative, feasible technology to aid in various surgical steps while performing a MFC flap for posttraumatic avascular proximal scaphoid pole. It enhances the surgeon's perception of complex patient-specific pathologies and intraoperative accuracy. Especially, we emphasize the benefit of a handlebar on the 3D model, because it enormously improves its maneuverability and usability.